Empowering Sustainable E-Waste Recycling through Reverse Vending Machine Adoption among Generation Z in Malaysia - Hasbullah, Nornajihah Nadia; Kiflee, Ag Kaifah Riyard; Andrew, Jasmine Vivienne; Ambad, Sylvia Nabila Azwa; Budin, Dg Kamisah Ag; Ramachandran, K.K (International Review of Management and Marketing, 2026)
The accelerating generation of electronic waste (e-waste) presents substantial environmental and public health challenges, particularly in developing economies with weak household-level management systems. In Malaysia, the rapid diffusion of electronic products has increased the urgency for efficient, scalable, and user-oriented e-waste collection mechanisms. Reverse vending machines (RVMs) represent a decentralised and incentive-based technological solution, yet empirical evidence explaining their adoption for e-waste recycling remains limited. Grounded in Rogers’ Diffusion of Innovations theory, this study examines the determinants of e-waste RVM adoption intention among Generation Z university students in Malaysia. Sustainable awareness was included as a moderating variable to evaluate the influence of environmental values on adoption behaviour. Data from 153 respondents were gathered using a quantitative cross-sectional survey and evaluated using Partial Least Squares Structural Equation Modelling (PLS-SEM). The results indicate that trialability significantly enhances adoption intention. In contrast, relative advantage, complexity, compatibility, and observability do not demonstrate significant direct effects. Furthermore, sustainable awareness significantly strengthens the relationship between trialability and adoption intention. This indicates that environmentally aware individuals are more inclined to translate experiential interaction into adoption behaviour. Overall, the results emphasise the significance of hands-on exposure and sustainability-oriented values in promoting technology-enabled e-waste recycling among digitally native cohorts. This study extends the Diffusion of Innovations framework by demonstrating the conditional role of sustainable awareness in the adoption process. It also provides practical implications for policymakers and practitioners to prioritise pilot initiatives, experiential engagement, and targeted sustainability communication strategies.